2006
DOI: 10.1097/01.pas.0000213311.28682.b2
|View full text |Cite
|
Sign up to set email alerts
|

Solid and Pseudopapillary Tumor of the Pancreas—Review and New Insights Into Pathogenesis

Abstract: Solid pseudopapillary tumors (SPT) of the pancreas are rare neoplasms that occur mostly in young women. Despite of a low malignant potential, 10% to 15% of the cases have aggressive behavior with metastatic dissemination possibly leading to death. To date, no pathological factor can reliably predict the outcome of these tumours. Galectin-3, a major actor in the carcinogenesis of pancreatic ductal adenocarcinoma, has not been investigated in SPT. The presence of progesterone receptors is frequently reported in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(74 citation statements)
references
References 36 publications
2
70
1
1
Order By: Relevance
“…The use of 'traditional' ER antibodies with no anti-b activity could explain why ER has previously been scarcely found in pancreatic tumours. ERb is reported to be relatively more expressed than ERa in papillary cystic neoplasms of the pancreas (Morales et al 2003), solid pseudopapillary tumours (Geers et al 2006) and human pancreatic cancer cell lines (Konduri & Schwarz 2007). Our study shows for the first time that there is a considerably high expression of ER in human insulinomas and it is predominantly of the ERb isoform.…”
Section: Discussionmentioning
confidence: 54%
“…The use of 'traditional' ER antibodies with no anti-b activity could explain why ER has previously been scarcely found in pancreatic tumours. ERb is reported to be relatively more expressed than ERa in papillary cystic neoplasms of the pancreas (Morales et al 2003), solid pseudopapillary tumours (Geers et al 2006) and human pancreatic cancer cell lines (Konduri & Schwarz 2007). Our study shows for the first time that there is a considerably high expression of ER in human insulinomas and it is predominantly of the ERb isoform.…”
Section: Discussionmentioning
confidence: 54%
“…É mais comum em pacientes na segunda e terceira décadas de vida, com (8) , ocorrendo na maioria dos casos no sexo feminino (2,3,(6)(7)(8)(9)(10) , contrapondo-se ao presente estudo, com paciente do sexo masculino de 37 anos. Devido a essa predominância no sexo feminino foi proposto que os hormônios sexuais pudessem fazer parte da gênese tumoral, entretanto ensaios imuno-histoquímicos não são unânimes na demonstração de receptores de estrógeno nessas células.…”
Section: Discussionunclassified
“…Other investigators found differences in IHC pattern between primary and secondary deposits of SPN. Geers et al observed weak/negative CD10, CD56, galectin-3 and PR staining in liver metastasis of SPN [70]. In other report, primary SPN and metachronous liver metastasis showed focally positive and negative CD10 staining, respectively [22].…”
Section: Discussionmentioning
confidence: 99%
“…Some nuclear morphometric features may also be useful for prediction of clinical aggressiveness of SPN as well [69]. Some researchers tested IHC stains as potential predictors of aggressive behavior: CD10, CD56, PgR, synaptophysin, p53, Ki-67, α1-antitrypsin, α1-antichymotrypsin, neuron-specific enolase, galectin-3, vimentin, chromogranin, pan-cytokeratin, Cam5.2, and epithelial membrane antigen (EMA) [11,24,32,33,70,71].…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation